Kemampuan Menulis Teks Persuasif pada Siswa Kelas IV di SDN 13 Limo Suku Kabupaten Agam - Dina Rahmadani; Indah Irgandi; Nur Hafizah; Ranti Julia (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This study aims to evaluate the ability to write persuasive texts in elementary school students. The main focus of the research is to analyze students' abilities in terms of text structure, linguistic rules, and characteristics of language use. The research method used is quantitative descriptive with the main instrument being a written test. The research subjects were four grade students at SDN 13 Limo Suku, Agam Regency. The research results show that: (1) In terms of text structure, the majority of students are able to write well, although some still experience difficulties in organizing arguments logically and coherently. (2) In terms of linguistic rules, students show a fairly good understanding, especially in the correct use of spelling and grammar, although there are some deficiencies in vocabulary variations and the use of complex sentences. (3) In terms of the characteristics of language use, students tend to be able to use persuasive language, but need more practice to improve rhetorical skills and the attractiveness of writing. Overall, the ability to write persuasive texts for fourth grade elementary school students at SDN 13 Limo Suku, Agam Regency is in the quite capable category. These findings indicate the need for improvement in learning to write persuasive texts, with a focus on strengthening argument structures and using more varied and effective language. It is hoped that this research can become the basis for developing more effective learning strategies in improving students' persuasive writing skills at the elementary school level.